2020
DOI: 10.1016/j.afjem.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patient experience in the emergency department: A scoping review

Abstract: Introduction Measuring patients' experience in the emergency department can be an avenue through which the patients are able to evaluate their own care experience, and this may provide guidance for healthcare professionals in addressing quality improvement. This scoping review aimed to identify and examine existing tools that measure patients' experience in the emergency department. Methods A scoping review was carried out to synthesize evidence from a range of studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Several recent literature reviews and studies7–12 confirmed these findings and identified other factors that can have an impact on patient satisfaction, which include waiting times; communication and information sharing; empathy and attitudes; technical competence; cultural aspects such as patient characteristics, pain, and the ED environment (eg, volume, staff, space, complexity of injuries and medical conditions, and intensive treatment in the ED); and patient-centered care.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Several recent literature reviews and studies7–12 confirmed these findings and identified other factors that can have an impact on patient satisfaction, which include waiting times; communication and information sharing; empathy and attitudes; technical competence; cultural aspects such as patient characteristics, pain, and the ED environment (eg, volume, staff, space, complexity of injuries and medical conditions, and intensive treatment in the ED); and patient-centered care.…”
mentioning
confidence: 79%
“…6 This review showed that factors such as provider-patient interpersonal factors, perceived waiting times, and providing information to patients are related to patients' perceptions and predictors of satisfaction. 6 Several recent literature reviews and studies [7][8][9][10][11][12] confirmed these findings and identified other factors that can have an impact on patient satisfaction, which include waiting times; communication and information sharing; empathy and attitudes; technical competence; cultural aspects such as patient characteristics, pain, and the ED environment (eg, volume, staff, space, complexity of injuries and medical conditions, and intensive treatment in the ED); and patient-centered care.…”
mentioning
confidence: 83%
“…A number of tools measuring patients and family member's experience and/or satisfaction with the care they received in the ED have been developed and used globally. Recently conducted scoping reviews to identify and examine such tools used in the ED [20 , 21] found nine (9) surveys used globally to measure adult patients experience and three (3) for family members. Furthermore, measuring patient and family member's experience of the ED is relatively new compared to that of the intensive care unit (ICU) which has been explored extensively [22] .…”
Section: Tools Currently Used To Measure Patient and Family Experienc...mentioning
confidence: 99%
“…2021 Saudi-Arabia Arrival Waiting time, and urgency of treatment Medications Pain management Follow-ups on tests/results Interpreter services Nursing care Doctor care Discharge Overall rating Likelihood to recommend 23 items Telephonic questionnaire After discharge from the ED Emergency Department Patient Satisfaction Assessment (EDPSA) Mohammadi-Sardo, M.R & Salehi, S Iran Tangibles Reliability Responsiveness Assurance Empathy 24 items + 1 open-ended question Self-completed questionnaire At ED - 7 days post-discharge Patient Satisfaction of Emergency Department Survey by Omidvari & Tajik Zohrevandi, B & Tajik, H 2014 Iran Physical comfort and residential aspects Physicians care Nurse care Behavioral aspects Waiting time for service presentation 37 items Self-completed questionnaire After discharge Patient Experience of Care Survey Chiu, H et al. 2014 Canada Arrival in the ED Waiting time Doctors & Nurses Your care & Treatment Leaving the ED Overall experience 9 items + 1 open-ended question Self-completed & mailed questionnaire and the interview question is completed by a research assistant Immediately upon discharge from the ED and at home Press Ganey Questionnaire (PGQ) Soleimanpour, H 2011 Iran Identification and waiting time Registration process, physical comfort and nursing care Physician care Overall satisfaction with the ED 30 items Self-completed questionnaire At home post discharge *Oyegbile and Brysiewicz [21] . …”
Section: Tools Currently Used To Measure Patient and Family Experienc...mentioning
confidence: 99%
“…Clinical settings, in general, and emergency departments (EDs), in particular, have long been described as complex, overwhelming, and stressful environments ( Aaronson et al, 2018 ; Boyle et al, 2012 ; Gordon et al, 2010 ; Sonis et al, 2019 ; Ulrich, 1991 ). EDs are further characterized by high patient volumes, rising service demands, overburdened staff, and an atmosphere of continual exigency ( Brysiewicz & Emmamally, 2017 ; Cypress, 2014 ; Oyegbile & Brysiewicz, 2020 ). While diverse structural and process elements constitute this environment, the ED is typically designed to prioritize its main function, that is, to save lives and minimize morbidity ( Bailey et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%